PENGGUNAAN MEDIA GAMBAR UNTUK MENINGKATKAN AKTIVITAS BELAJAR SISWA DALAM PEMBELAJARAN SEJARAH : Penelitian Tindakan Kelas di Kelas XI IIS 3 SMA Negeri 24 Bandung - Riane Wildy Hernanda, - (2017)
Abstract:This research is called the use of image as media in teaching history to increase the activity of student's learning: An action research of class XIIIS 3 SMAN 24 Bandung. The study is based on the discovery of trouble as researchers conducted pra-research observation.The researchers found many students who did not contribute to learning process held, there are some students who asked, respond and answer questions from teachers. So the learning process impressed taken place in a one direction, it will be from teachers to students then it ended with the implementation of competency test the project by the students.It made of learning which presented by the teacher has less meaningful.In order to do this through research, this researcher could want to increase the activity of of students to study with the use of the image as media. Thatimage media been disclosed in the research which was going to help students to seek for informations, then discuss it with the group and then present it in front of the class. The methodology that used in this research is classroom action research which is designed by Kemmis and Taggart. The design of this model had several stages were plan (planning), act (the implementation), observe (observation) and reflect (reflection).The actionimplemented 3 times because of to the third actionof activity students in learning historywas already high .In addition the technique of collecting data which used of this study are observation and conducting interviews .While an instrument collecting data which used of these tests are field notes , observation guidelines , and interview guidelines.Based on the results of this research, the use of mediaimages in teaching history could increase up the activity of students to study in the class XI IIS 3 SMAN 24 Bandung given the recent increase in the percentage on each cycle.In fact there were several problems that will emerge during the research phase is the students who are used to obtain any information that later on must seek for the information and make students to interested involved in the process of learning.